A comparison of leg-to-leg bioelectrical impedance and skinfolds in assessing body fat in collegiate wrestlers - Utter, A. C.; Scott, J. R.; Oppliger, R. A.; Visisch, P. S.; Goss, F. L.; Marks, B. L.; Nieman, D. C.; Smith, B. W. (The Journal of Strength and Conditioning Research, 2001)
A comparison of the leg-to-leg bioelectrical impedance (BIA) system and skinfold analysis in estimating % body fat in a large number of National Collegiate Athletic Association (NCAA) collegiate wrestlers was conducted. A series of 5 cross-sectional assessments, including the NCAA Division I and III Championships, were completed throughout the 1998-1999 wrestling season with samples ranging from (N = 90-274). Body density was determined from the 3 skinfold measures using the Lohman prediction equation. BIA measurements were determined using the Tanita body fat analyzer, model 305. Significant correlations between methods ranging from (r = 0.67-0.83, p < 0.001) and low standard error of estimates (SEE) for % body fat ranging from 2.1-3.5% were found throughout the 5 assessment periods. This preliminary study demonstrated that the leg-to-leg bioelectrical impedance system accurately estimated % body fat when compared to skinfolds in a diverse collegiate wrestling population.